Flypaper Effect pada Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU), dan Dana Alokasi Khusus (DAK) terhadap Belanja Daerah Kabupaten/Kota di Kalimantan Barat - Tifanny, Tifanny (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study aims to analyze the effect of Regional Original Revenue (PAD), General Allocation Fund (DAU), and Special Allocation Fund (DAK) on Regional Spending and to identify the occurrence of the flypaper effect phenomenon in regencies/cities in West Kalimantan Province during the 2018–2022 period. This research employs a quantitative approach with a causal comparative research design. The population consists of 14 regencies/cities in West Kalimantan Province, with a saturated sampling technique resulting in 70 observations based on secondary data obtained from Regional Budget Realization Reports. Data analysis was conducted using descriptive statistical analysis and multiple linear regression analysis with SPSS version 25. The results indicate that Regional Original Revenue, General Allocation Fund, and Special Allocation Fund have a positive and significant effect on Regional Spending, both simultaneously and partially. Furthermore, the study confirms the existence of the flypaper effect phenomenon, as the contribution of intergovernmental transfer funds consisting of General Allocation Fund and Special Allocation Fund is greater than the contribution of Regional Original Revenue in financing Regional Spending. These findings indicate that local governments in West Kalimantan still demonstrate a considerable level of dependence on central government transfers in financing regional expenditures.